2013
DOI: 10.1007/s12526-013-0187-y
|View full text |Cite
|
Sign up to set email alerts
|

An inverse latitudinal biodiversity pattern in asellote isopods (Crustacea, Peracarida) from the Southwest Atlantic between 35° and 56°S

Abstract: An inverse latitudinal biodiversity pattern in asellote isopods (Crustacea, Peracarida) from the Southwest Atlantic between 35°a nd 56°S

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…an increase of species richness with higher latitude (e.g. in the North Sea, Heip et al, 1992;Rees et al, 1999; along the Argentina coasts, Doti et al, 2014) or a bell-shaped trend (Gray, 2000;Hummel et al, 2016). Our study revealed a more complex pattern: a bell-shaped curve peaking in Brittany between 47°N to 49°N latitude (Figure 4).…”
Section: Accepted Manuscriptsupporting
confidence: 44%
“…an increase of species richness with higher latitude (e.g. in the North Sea, Heip et al, 1992;Rees et al, 1999; along the Argentina coasts, Doti et al, 2014) or a bell-shaped trend (Gray, 2000;Hummel et al, 2016). Our study revealed a more complex pattern: a bell-shaped curve peaking in Brittany between 47°N to 49°N latitude (Figure 4).…”
Section: Accepted Manuscriptsupporting
confidence: 44%
“…The fact that more species are described in the southern region of the Argentine Sea could be attributable to the concentration of oceanographic campaigns that were performed by international initiatives when travel to Antartica or passing from Pacific to Atlantic Ocean (around Tierra del Fuego and Southern Islands). The major biodiversity encountered in the southern tip of the Southwest Atlantic also could be attributable to an inverse biodiversity pattern that was previously registerd in Southwest Atlantic higher latitudes for some intertidal rocky shore invertebrates (Palomo et al 2011) or other taxa as asellote isopods (Doti et al 2014). The increasing in biodiversity in high latitudes could also be attributable to the presence of high extentions of hard bottoms that permit the settlement of invertebrates and the fact that most Magellanic species that occur in southern Chile extend to the Southwest Atlantic (López Gappa et al 2006).…”
Section: Discussionmentioning
confidence: 70%
“…In the south-west Atlantic, between 35° and 56°S, the species richness of asellote isopods is remarkably high south of 47°S (Doti et al , 2014). The three new species described herein were found at lower latitudes (37°–45°S), Pentaceration pleonarietis sp.…”
Section: Discussionmentioning
confidence: 99%
“…nov. and N. argentinenesis sp. nov. were collected deeper than 100 m. Based on the biodiversity patterns of the different invertebrate groups two biogeographic provinces have been recognized in the Argentine Sea, viz: the Argentine Biogeographic Province and the Magellan Biogeographic Province (ABP and MBP, respectively) (Doti et al , 2014; and references therein). An exact limit between these two provinces is difficult to ascertain, Roux et al (1988) studying the distribution of molluscs and echinoderms found that off Mar del Plata (38°–39°S) the transitional area between the ABP and the MBP occurs at a depth of around 76–81 m. Thus, N. argentinensis and N. bicarinatus could be considered as members of the magellan assemblage whereas P. pleonarietis could be part of any of the two assemblages since it was found in the transitional area of both biogeographic provinces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation